Etiquette and Protocol in Public Relations Activities - Belliana Rahma Fitriani Bella; Andien Dwi Mayasari; Alfina Alfina (Journal of Humanities Research Sustainability, 2024)
Background. Etiquette and protocols play an important role in the practice of public relations activities, ensuring effective communication and harmonious relationships with various related parties. Understanding and applying these principles not only affects the reputation of the organization, but also reflects the professionalism of a PR practitioner. Purpose. The study aims to explore an in-depth understanding of the importance of etiquette and protocol in the practice of public relations activities, as well as to provide practical guidance for public relations professionals in strengthening their communication strategies. Method. The approach used is a literature review, by identifying, evaluating, and synthesizing literature from various sources such as books, journals, and scientific articles that are relevant to the theme of etiquette and protocol in the context of public relations. Results. Literature analysis reveals that etiquette and protocols play a crucial role in shaping organizational image, managing crises, and building positive relationships with various stakeholders. Proper implementation of etiquette and protocols not only improves the effectiveness of communication, but also minimizes the risk of misunderstandings and conflicts. Conclusion. The importance of understanding and implementing etiquette and protocols in public relations activities cannot be doubted. Public relations professionals need to consider the ethical aspects and cultural values of communication, as well as maintain consistency in the implementation of protocols to build sustainable and mutually beneficial relationships with the public, clients, and other stakeholders. This conclusion underscores the need for a holistic and strategic approach to managing an organization's reputation and communication through the judicious use of etiquette and protocols in every interaction.